2011
DOI: 10.1371/journal.pone.0020349
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Aerolysin Family: From Bacteria to Vertebrates

Abstract: A number of bacterial virulence factors have been observed to adopt structures similar to that of aerolysin, the principal toxin of Aeromonas species. However, a comprehensive description of architecture and structure of the aerolysin-like superfamily has not been determined. In this study, we define a more compact aerolysin-like domain – or aerolysin fold – and show that this domain is far more widely spread than anticipated since it can be found throughout kingdoms. The aerolysin-fold could be found in very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 73 publications
5
149
0
Order By: Relevance
“…1B). Indeed, the aerolysin domain-containing proteins are widely distributed, from bacteria to vertebrates (9) (Table S1). Specifically, the aerolysin domain of βγ-CAT showed high similarity to the aerolysin domains of other vertebrate proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B). Indeed, the aerolysin domain-containing proteins are widely distributed, from bacteria to vertebrates (9) (Table S1). Specifically, the aerolysin domain of βγ-CAT showed high similarity to the aerolysin domains of other vertebrate proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NLR-dependent (NLRP3-dependent in mammals) caspase-1 activation and IL-1β release have been associated with destabilization of the lysosomal membrane and activation of lysosomal proteases (specifically, cathepsin B) (6). The βγ-CAT α-subunit consists of structural elements that tend to undergo oligomerization and insert into the membrane to form pores (9,30,31). Previous studies have shown that, whereas the β-subunit of βγ-CAT is most likely responsible for binding to cells via "protein" receptor(s), its α-subunit formed transmembrane pores in anucleate erythrocyte and platelet membranes, which resulted in rapid K + efflux (10,11,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the aerolysin family of proteins, the conserved beta sheet dominated aerolysin fold is believed to adopt a barrel conformation within a membrane with the associated domains primarily having a binding role (Szczesny et al, 2011). It is conceivable that despite the diversity in primary sequence, many of the non 3-domain Cry toxins could share significant structural/functional homology.…”
Section: Convergent Evolution Of the Beta Sheet Toxins?mentioning
confidence: 99%